New and little known taxa of the genus Calopsyra Brunner von Wattenwyl, 1891 (Orthoptera: Tettigoniidae: Phaneropterinae) from Indo-Malayan Region - A.V. Gorochov (Кавказский энтомологический бюллетень, 2023)
A new material on the Indo-Malayan genus Сalopsyra Brunner von Wattenwyl, 1891 from the tribe Holochlorini is reviewed. This genus is divided into three subgenera: Calopsyra s. str., Parapsyra Carl, 1914, stat. n. (previously considered as a distinct genus) and Rhodopsyra subgen. n. Eight new combinations are proposed: C. (P.) notabilis (Carl, 1914), comb. n., C. (P.) nigrovittata (Xia et Liu, 1992), comb. n., C. (P.) midcarina (Liu et Kang, 2006), comb. n., C. (P.) nigrocornis (Liu et Kang, 2006), comb. n., C. (P.) fuscomarginalis (Liu et Kang, 2006), comb. n., C. (P.) brevicauda (Liu, 2011), comb. n., С. (Rh.) muricetincta (Karny, 1926), comb. n., C. (Rh.) laticauda (Karny, 1926), comb. n. Two new species from Borneo and Sumatra are described: C. (C.) sexmaculata sp. n. and C. (Rh.) roseoalata sp. n. The neotype for C. (C.) octomaculata (Westwood, 1848) is designated, and this species is redescribed in accordance with new data.